Ethnic America - Weiser, Marjorie P. K. (New York Wilson, 1978)
A compilation of reprinted articles considering various ethnic groups in the United States, with emphasis in Native American and Afro-American, and how they coped with their problems in adjusting to the dominant cultures.
Keywords: Minorities -- United States; Ethnicity